Synthesis and Antimicrobial Activity of Bis[2-(substituted phenyl)-5-carboxy methyl 4-Thiazolidinone] Derivatives of Dapsone - Srinivasa Rao, N.; Rao, J.T. (Asian Journal of Chemistry, 2016)
Some 4-thiazolidinone derivatives were synthesized from Schiff base and screened for their antimicrobial activity against E. coli, Bacillus subtilis, Tricoderma viridate and Aspergillus niger.